2020
DOI: 10.35848/1347-4065/abbb20
|View full text |Cite
|
Sign up to set email alerts
|

Low-stress diamond-like carbon films containing carbon nanoparticles fabricated by combining rf sputtering and plasma chemical vapor deposition

Abstract: Carbon nanoparticles (CNPs) incorporated diamond-like carbon (DLC) films have been fabricated by a combination of rf sputtering and plasma chemical vapor deposition. Spherical CNPs with a mean size of 21.2 nm are sandwiched between DLC layers with a mass density of 1.7 g cm−3. The film stress is decreased to 119 MPa, by depositing the CNPs over the base DLC layer at a surface coverage of 10.7%. This reduction is approximately half of that without CNPs. Raman spectroscopy indicates the insertion of CNPs barely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Raman spectra clearly show the separated D (1350 cm −1 ), and G (1580 cm −1 ) bands. The area intensity ratio of D/G band was around 1.8; this indicates the structure of the CNPs were polymer like a-C:H [25,[28][29][30]. Similar spectra were also observed at other FRs.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Raman spectra clearly show the separated D (1350 cm −1 ), and G (1580 cm −1 ) bands. The area intensity ratio of D/G band was around 1.8; this indicates the structure of the CNPs were polymer like a-C:H [25,[28][29][30]. Similar spectra were also observed at other FRs.…”
Section: Resultssupporting
confidence: 72%
“…The surface-modified nanoparticles showed multi-exciton generation, which is necessary to increase solar cells' efficiency [18]. We recently used MHDPCVD to produce carbon nanoparticles [23][24][25] and confirmed that pressure played an important role in size control [23]. These studies revealed the essential parameters for the size control, while the growth mechanism was unclear.…”
Section: Introductionmentioning
confidence: 89%
“…One potential technique is thermal spray coatings using a stream of feedstocks which is dependent on the thermal expansion gradient between the top coat and the substrates [11,12]. Another promising method is physical vapor deposition (PVD) which provides various coating layers because it has few restrictions on source materials and the formation of multi-layers [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%